Serological profile of acute undifferentiated fever cases attending a tertiary care hospital: emergence of scrub typhus in Telangana State - Dr. Md Khaleel; Dr. Md Wajid (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Present study was undertaken to elucidate aetiology of acute undifferentiated fevers and prevalence of scrub typhus among patients admitted in our hospital. Materials & Methods: 100 consecutive serum samples received during the period May 2016 to October 2016 were tested for dengue NS1 antigen by ELISA, chikungunya Ig M antibodies by MAC- ELISA, widal tube agglutination test, leptospira Ig M antibodies by ELISA, plasmodium falciparum, plasmodium vivax, by Parahit F and V,Weil Felix tube agglutination test, orientiatsusugamushi IgM and IgG antibodies by Immunochromatography. Results: Out of hundred samples subjected to more extensive analysis, 39 samples were positive for Dengue which included 28 samples positive for IgM antibodies, 6 samples were positive for IgM antibodies and NS1 antigen, 5 positive for NS1 antigen. 19 were found to be positive for antibodies to orientiatsusugamushi by Immunochromatography. Conclusion: Though the dengue fever is often considered and investigated by the physicians in all such cases, other infections are often ignored or do not figure in the differential diagnosis particularly during outbreaks. There is a need to investigate for scrub typhus, an acute febrile illness caused by Orientia tsusugamushi (Ricketssia tsusugamushi) which is a re-emerging disease in India.